Notes and queries - Oxford University Press (Oxford University Press, 1849)
"Founded under the editorship of the antiquary W J Thoms, the primary intention of Notes and Queries was, and still remains, the asking and answering of readers' questions. It is devoted principally to English language and literature, lexicography, history, and scholarly antiquarianism. Each issue focuses on the works of a particular period, with an emphasis on the factual rather than the speculative. The journal comprises notes, book reviews, readers' queries and replies." --Oxford Journals website viewed 25 February 2016.
Keywords: Questions and answers : Periodicals